QUALITY MANAGEMENT: CASE STUDY AT GUDEG PEJOMPONGAN RESTAURANT USING TQM TOOLS - Putro, Bima Pramono; fitriani, katlea (Universitas Katolik Parahyangan, 2024)
In production, quality management is used to create items that meet quality requirements, avoid product reprocessing, etc. One of the quality management systems that Rumah Makan Gudeg Pejompongan does not have in place is statistical quality control. The purpose of this study is to determine the process of making the final product, namely gudeg, knowing the types of failures that often occur in products produced in one month, knowing the order of the types of product failures that occur most often in one month, and knowing the causes of failure of gudeg products produced in restaurants. Four of the first seven TQM tools—flowcharts, check sheets, Pareto charts, cause and effect diagrams, or fishbone diagrams—are used in this study to assist businesses in implementing quality management. The author employed a descriptive research methodology, gathering data directly from field sources (field research). Cross-sectional data collection is used in this study to gather information at a single point in time. Interviews, observations, and literature reviews are used to collect data, while statistical tools are used for data analysis on Total Quality Management. The findings indicate that the Gudeg Pejompongan restaurant's production process consists of 19 steps to produce the finished product. Failures in the production process come in different forms, and the quantity of production failures is evident throughout the night and morning shifts. Out of 84 units of product failures, the categories of failures and their corresponding order of largest to smallest are as follows: Failure C (burnt jackfruit) accounts for 33%, failure D (hard jackfruit) for 29%, failure B (crushed krecek crackers) for 20%, and failure A (egg filling out) for 18%. Furthermore, the findings indicated that processes and human resources are the main reasons behind product failures at the Gudeg Pejompongan restaurant.